Tracheal transection after blunt trauma by motor vehicle accident: A diagnostic and survival challenge - Huda, AK Qumrul; Hoque, Rezwanul; Sing, Wong Poo (Bangladesh Critical Care Journal, 2015)
Tracheal transection is a rare injury after blunt trauma. Complete disruption of the trachea is rare, with a reported incidence of 1 in 4491 trauma admission. Blind oral or nasal intubation in patients with tracheal injury can lead to false extra passage. The presence of tracheal transection in the intubated ventilating patient is rarer and constitutes a major diagnostic and survival challenge. Here we present a case of tracheal transection caused by motor vehicle accident diagnosed few days later of the incidence by Computed tomography (CT) of chest, who went for thoracotomy and anastomosis of tracheal transection but developed anastomosis dehiscence. Repeated trial for anastomosis could not save the life of the patient because of development of severe sepsis, disseminated intravascular coagulation (DIC) and multi organ dysfunction syndrome (MODS). Early diagnosis by CT of chest and tracheal anastomotic surgery as early as possible (possibly within 24 hrs) before development of sepsis from mediastinitis is paramount for survival of patient. Bangladesh Crit Care J March 2015; 3 (1): 31-32